ANALISIS PENGARUH SUDUT ELEVASI PANEL SURYA 50 WP TIPE MONOCRISTALLINE SILICON TERHADAP DAYA KELUARAN - Elvando Putra Nugroho; Fakhriy Hario Partiansyah; Gaguk Asmungi (Jurnal Mahasiswa TEUB, 2023)
The potential for solar energy in Indonesia is very profitable if it can be utilized properly and correctly. However, in its application as a power plant, solar panels often encounter problems where the output power generated from solar panels is often less than optimal, so that it will affect the supply of power to the load. The purpose of this study was to determine the effect of theelevation angle of the solar panel on the output power of the 50 WP monocrystalline silicon type solar panel and to determine the installation of solar panels that can produce high output power. The results obtained from this study by adjusting the elevation angle of the solar panel with the HRA (Hour Angle) angle for each hour of solar irradiation can maximize the maximum output power for each hour of irradiation. In addition, another solution for installing solar panels can be done by using the HRA12 angles as an alternative angle for installing solar panels, which in this study obtained an average radiation intensity during solar irradiation hours of 18.22%. Index Terms— Elevation Angle, Output Power, Monocristalline Sillicon, Solar Panel.